Rural/Urban Area Differences in the Cognitive Abilities of Primary School Children in England. Issue 2 (16th September 2013) - Midouhas, Emily; Flouri, Eirini
Abstract: Recent research finds that the higher academic performance of rural adolescent pupils in England is due primarily to selection. Yet little is known about whether this applies to primary school children. This study examined the cognitive abilities of primary school children in areas with varying levels of rural and urban settlement, after accounting for factors associated with children's abilities and families' selection into areas. Remaining differences were investigated with area human capital, based on the percentage of residents with a university degree. These relationships were tested using data from the UK's Millennium Cohort Study. Cognitive abilities were measured at age 7 with the British Ability Scales II and the National Foundation for Education Research Progress in Maths 7 test. Two‐level regression models were fitted whereby children were nested within local authority districts. After adjustment, there were no area differences in maths scores. However, children in areas with a mix of rural and urban settlement had higher non‐verbal scores, explained by the level of area human capital. Children in major urban areas such as London had higher reading scores, a difference unexplained by area human capital. Selection explained most rural/urban area differences in young children's cognitive abilities in England. However, the presence of university‐educated adults in an area may be an important pathway of some rural/urban area 'effects'. Copyright © 2013 John Wiley & Sons, Ltd.